(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article looks at the specific features of the usage of borrowed Anglicisms in Russian texts and their perception by native speakers of Russian. Analysis of relevant linguistic studies in the sphere of media linguistics and borrowings, media texts, as well as lexicographic resources capturing the expansion of the thesaurus of the Russian language due to borrowings, shows that one of the stylistic features of the modern media is a growing number of only partly assimilated borrowings from the English language, including lexemes that form the value system guiding native speakers of the recipient language. The purpose of introducing borrowings into media texts is the attraction of the audience’s attention. However, it appears that the effect produced by borrowings on an average recipient is controversial. In order to test the suggested hypothesis, the authors examine the specific features of the usage of partly assimilated borrowings in media texts that refer to the issues of tolerance and their derivatives (bullying, cyberbullying, abuse, ageism, etc.).